2019
DOI: 10.3390/min9060356
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Scale Pore Structure and Fractal Dimension of Longmaxi Shale in the Upper Yangtze Region, South China: A Case Study of the Laifeng–Xianfeng Block Using HIM and N2 Adsorption

Abstract: This paper tries to determine the key evaluation parameters of shale reservoirs in the complex tectonic provinces outside the Sichuan Basin in South China, and also to target the sweet spots of shale reservoirs accurately. The pore-structure characteristics of the Lower Silurian Longmaxi shale gas reservoirs in Well LD1 of the Laifeng–Xianfeng Block, Upper Yangtze region, were evaluated. N2 adsorption and helium ion microscope (HIM) were used to investigate the pore features including pore volume, pore surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…(2) In the Late Hercynian, a series of marine carbonate deposition and marine-continental transitional coal-sedimentation layers were formed with an average thickness of 500 m. (3) During the Indosinian period, the Sichuan Basin experienced a transition from marine to continental sedimentation and the thickness of Triassic strata was approximately 1200 m. (4) During the Yanshanian period, approximately 2900 m of continental deposits were formed spanning from the Jurassic to the Cretaceous. (5) During the Himalayan period, the sedimentary caprock in the area was fully folded and fractured, forming the current tectonic features.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) In the Late Hercynian, a series of marine carbonate deposition and marine-continental transitional coal-sedimentation layers were formed with an average thickness of 500 m. (3) During the Indosinian period, the Sichuan Basin experienced a transition from marine to continental sedimentation and the thickness of Triassic strata was approximately 1200 m. (4) During the Yanshanian period, approximately 2900 m of continental deposits were formed spanning from the Jurassic to the Cretaceous. (5) During the Himalayan period, the sedimentary caprock in the area was fully folded and fractured, forming the current tectonic features.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The black shales from the Wufeng Group (O 3 w) and the Longmaxi Group (S 1 l) are considered to be the most developed shale strata in China [1][2][3][4][5]. It has been proven by reservoir exploration and development that reservoir overpressure is an important indicator dominating the shale gas enrichment and production in southern China [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the techniques for quantitative analysis of shale pore systems [4,[12][13][14], low-pressure gas adsorption (LPGA) is important in the measurement of pore properties over a wide range of pore sizes. Low-pressure N 2 adsorption is frequently used to analyze mesopore characteristics in shale reservoirs [15]. One of reasons is that mesopores are usually much more than micropores and macropores in shale reservoirs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers [22][23][24][25][26][27] in this special issue focus on energy geology, addressing the structure and composition of coal and shale nanominerals as well as changes in nanopores and their fractal dimensions. They also describe structural characteristics such as the size, shape, and connectivity of nanopores in unconventional oil and gas reservoirs, along with their evolutionary laws and control factors.…”
mentioning
confidence: 99%
“…The findings indicated that the composition content porosimetry porosity generally increases with increasing OM and clay content and decreases with increasing quartz and feldspar content. Huang and coauthors [23] evaluated the pore structure characteristics of Lower Silurian Longmaxi shale gas reservoirs in Well LD1 of the Laifeng-Xianfeng Block, Upper Yangtze region in South China. N 2 adsorption and helium ion microscope (HIM) were used to investigate various pore features, including pore volume, pore surface area, and pore size distribution.…”
mentioning
confidence: 99%